PROGRAMLAMA ÖĞRETİMİNİN BİLGİ İŞLEMSEL DÜŞÜNME BECERİSİNE ETKİSİ. - ALSANCAK SIRAKAYA, Didem (Turkish Journal of Social Research / Türkiye Sosyal Araştırmalar Dergisi, 2019)
Students in the 21st century are expected to have various skills. One of these skills is the ability of computational thinking. Computational thinking involves solving problems, designing systems, and understanding human behavior, by drawing on the fundamental concepts of computer science. Computational thinking is a fundamental skill for everyone, not just for computer scientists. Different methods are used for the development of computational thinking skills. One of these methods is programming teaching. There are studies in literature in which programming impacted 21st century skills such as problem-solving, creativity and critical thinking. It is possible to think that it may be the effect of programming on computational thinking in the light of findings of researches. For these reasons, the aim of this study is to examine the effect of programming on students' computational thinking skills. The study group of the study is composed of 54 students who are taking the programming courses in the Computer Programming Department of Ahi Evran University's Vocational School of Technical Sciences in 2016-2017 Fall semester. Computational thinking scale is used as data collection tool. Descriptive statistics and associated samples t-test were applied in the analysis of the obtained data. At the end of the study, it was concluded that there was a significant difference between the pretest-posttest scores of the study group in terms of the score of computational thinking skills and this effect is independent of gender and programming skill level.